Autonomic nervous system dysfunction correlates with microvascular damage in systemic sclerosis patients. Issue 3 (October 2021) - Masini, Francesco; Galiero, Raffaele; Pafundi, Pia Clara; Gjeloshi, Klodian; Pinotti, Emanuele; Ferrara, Roberta; Romano, Ciro; Adinolfi, Luigi Elio; Sasso, Ferdinando Carlo; Cuomo, Giovanna
Objectives: Cardiac autonomic neuropathy is among the known cardiovascular complications of systemic sclerosis and may affect the whole prognosis of the disease. The aim of our study was to assess cardiac autonomic neuropathy prevalence in our cohort of systemic sclerosis patients and compare its main features with clinical and epidemiological data, particularly with the severity of microvascular damage, as detected by nailfold videocapillaroscopy. Methods: Twenty-six patients with definite systemic sclerosis were consecutively enrolled at our outpatient rheumatology clinic. All patients underwent physical examination, nailfold videocapillaroscopy, and autonomic neuropathy diagnostic tests (orthostatic hypotension test, deep breathing test, lying-to-standing, and Valsalva maneuvers). Results: Cardiac autonomic neuropathy prevalence was 50% (13 cases). On univariate analysis, cardiac autonomic neuropathy was shown to be significantly associated with an active pattern on nailfold videocapillaroscopy (odds ratio 5.86, 95% confidence interval 1.59–9.24; p = 0.032), whereas anti-Scl-70 positivity (odds ratio, 0.24; 95% confidence interval, 0.03–2.12; p = 0.049) and C-reactive protein (odds ratio, 19.32; 95% confidence interval, 1.79–56.71; p = 0.036) reached only a borderline statistical association. The time-dependent Cox multivariate regression model showed cardiac autonomic neuropathy development to be independently associated with an active pattern on nailfold videocapillaroscopy (odds ratio, 7.19; 95% confidence interval, 1.87–8.96; p = 0.042) and anti-Scl-70 positivity (odds ratio, 5.92; 95% confidence interval, 1.06–18.43; p = 0.048). Conclusions: Severe microvascular damage, as detected by nailfold videocapillaroscopy, may suggest the coexistence of autonomic dysfunction and should be considered as a red flag for the identification of patients particularly at risk of cardiac morbidity and mortality.